2014
DOI: 10.1073/pnas.1406391111
|View full text |Cite
|
Sign up to set email alerts
|

Scaling description of the yielding transition in soft amorphous solids at zero temperature

Abstract: Yield stress materials flow if a sufficiently large shear stress is applied. Although such materials are ubiquitous and relevant for industry, there is no accepted microscopic description of how they yield, even in the simplest situations in which temperature is negligible and in which flow inhomogeneities such as shear bands or fractures are absent. Here we propose a scaling description of the yielding transition in amorphous solids made of soft particles at zero temperature. Our description makes a connectio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

52
370
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(431 citation statements)
references
References 60 publications
52
370
5
Order By: Relevance
“…Our model is distinguished from the Random Field Ising Model in a crucial way: S i = ±1 can flip back to their original state, mediated by flips to S i = 0 even if the field is being increased monotonically, and the energy at a site does not approach the "flip" threshold monotonically. Recent studies [27] show that this feature affects the yielding transition, suggesting that our model is relevant for understanding the yielding of athermal materials. We have focused on the shear-induced rigidity aspect of athermal, particulate systems.…”
Section: Discussionmentioning
confidence: 79%
“…Our model is distinguished from the Random Field Ising Model in a crucial way: S i = ±1 can flip back to their original state, mediated by flips to S i = 0 even if the field is being increased monotonically, and the energy at a site does not approach the "flip" threshold monotonically. Recent studies [27] show that this feature affects the yielding transition, suggesting that our model is relevant for understanding the yielding of athermal materials. We have focused on the shear-induced rigidity aspect of athermal, particulate systems.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast to brittle materials, most real materials are often ductile to some degree and exhibit a complicated rheological creep response under constant applied loads [8][9][10][11]. To simplify the typical time-dependent creep response to constant applied loads that lead to failure, we can divide it into primary, secondary, and tertiary creep [12,13]: initial strain-hardening (described by the Andrade law) [14,15], steady-state or logarithmic creep [16], and a final phase in which the strain rate t increases, implying strain softening [17], finally leading to sample failure.…”
Section: Introductionmentioning
confidence: 99%
“…For amorphous solids the situation is instead less clear, and the microscopic understanding of the response to deformation and stress is a very active research topic. Several studies have revealed that even in the elastic regime the response is very jerky at low temperature, resembling very much the response of disordered magnetic materials [1][2][3][4][5][6] . Here we show that in a very large class of amorphous solids this behaviour emerges upon decreasing temperature, as a phase transition, where standard elastic behaviour breaks down.…”
mentioning
confidence: 99%